Antibacterial activity of polyphenol-rich pomegranate peel extract against Cronobacter sakazakii - Gökçe Polat Yemis; Susan Bach; Pascal Delaquis (International Journal of Food Properties, 2019)
The purpose of the study was to determine if pomegranate (Punica granatum L.) peel contains polyphenolic compounds with antibacterial activity against Cronobacter sakazakii. Minimum inhibitory and bactericidal concentrations of a methanolic extract were found to increase significantly (P < .05) with decreasing temperature (37, 21, 10 °C) and pH (6.0, 5.0, 4.0). Chemical analysis by high pressure liquid chromatography revealed that the elligitannins α- and β-punicalagin were most abundant hydrolysable polyphenolic compounds in the extract, followed by ellagic acid, ellagic acid derivatives and punicalin. Pomegranate peel is a potential source of natural preservatives for the control of Cronobacter sakazakii in food.